SPORTS CUPPING FOR SUPRASPINATUS TENDINOSIS: A CASE STUDY - Ahmed Helmy Saleh; Shahira Hassan; Mohamed F.F Bayomy; Tabish Ishaq Shaikh; Emad Ahmed Hussein (International Journal of Islamic and Complementary Medicine, 2024)
Supraspinatus tendinosis is a common source of shoulder pain. This tendinopathy is in most cases caused by an impingement of the supraspinatus tendon on the acromion as it passes between the acromion and the humeral head. Pain, and a decrease in range of motion, strength and functionality are the main complaints that accompany this injury. Being one of the well-established techniques, Sports wet cupping therapy (WCT) was used to treat a case of Supraspinatus tendinosis in this study. This paper aims to report the improved case of supraspinatus tendinosis using the treatment with sports cupping.  We used sports cupping therapy for treatment of this patient. This case is measured and assessed by visual analogue scale (VAS), shoulder range of motion (ROM) and shoulder physical examination. Results show the VAS decreased from 10 to 1 and the patient showed nearly full shoulder range of motion in forward flexion, abduction, extension, internal rotation and external rotation. In addition, the physical examination of shoulder and MRI was improved. Sports cupping treatment with wet cupping therapy is found to be helpful to relieve pain and recover function of shoulder joint.